2015
DOI: 10.1016/j.jdent.2015.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Clinical survival of indirect, anterior 3-unit surface-retained fibre-reinforced composite fixed dental prosthesis: Up to 7.5-years follow-up

Abstract: OBJECTIVES This prospective clinical study evaluated the performance of indirect, anterior, surface-retained, fibre-reinforced-composite restorations (ISFRCR). METHODS Between June-2003 and January-2011, a total of 134 patients (83 females, 51 males, 16-68 years old) received 175 ISFRCRs (local ethical registration number: 14/9/4). All restorations were made indirectly on a plaster model using unidirectional E-glass fibres (everStick CB, StickTech) in combination with a laboratory resin composite (Dialogue, Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 25 publications
0
30
0
1
Order By: Relevance
“…Two studies (Kumbuloglu & Ozcan ; Sailer et al. ) reported that none of the abutment teeth lost vitality during the observation period.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies (Kumbuloglu & Ozcan ; Sailer et al. ) reported that none of the abutment teeth lost vitality during the observation period.…”
Section: Resultsmentioning
confidence: 99%
“…FRC RBFPDs have a variable estimated 5‐year success rate ranging from 58.7% (Van Heumen 2009) to 94.9% (Kumbuloglu and Ozcan) . In both of those studies, the RBFPDs were replacing 1 anterior missing tooth utilizing 2 retainers.…”
Section: Discussionmentioning
confidence: 99%
“…12 FRC RBFPDs have a variable estimated 5-year success rate ranging from 58.7% (Van Heumen 2009) 11 to 94.9% (Kumbuloglu and Ozcan). 36 In both of those studies, the RBFPDs were replacing 1 anterior missing tooth utilizing 2 retainers. The significant differences in the success rate can be attributed to the technique sensitivity of the bonding procedure and the utilization of retentive features in the design of the prostheses.…”
Section: Technical and Biological Complicationsmentioning
confidence: 99%
“…[38] On the other hand, survival rate of ISFRCR in previous studies with other fibers and resin cements and veneering composites ranged between 93% up to 1 year in 31 patients [39] and 93.5-100% up to 58 months in 135 patients. [40] In none of these studies, clinical protocols were mentioned prior to adhesion protocols. Thus, future clinical studies should report whether contamination was experienced prior to adhesive cementation and what kind of the cleansing protocols was employed for resin composite materials in case of a failure.…”
Section: Discussionmentioning
confidence: 99%